Condylectomy and “surgery first” approach: An expedited treatment for condylar hyperplasia in a patient with facial asymmetry - López,Diego Fernando (2017)
ABSTRACT Condylar Hyperplasia (CH) is a self-limiting pathology condition that produces severe facial deformity at the expense of mandibular asymmetry. In this case report a 15-year-old female patient was diagnosed with Unilateral Condylar Hiperplasia (UCH) by mean of single-photon emission computed tomography (SPECT) and histological study. A high condylectomy in the right condyle was performed to stop the active status of the hyperplasia. A month after condylectomy, orthognathic jaw impaction and asymmetric mandibular setback surgery was performed with the Surgery First Approach (SFA). After 10 days, orthodontic appointments were made every two weeks during 4 months. The active phase of treatment lasted 14 months. Excellent facial and occlusal outcomes were obtained and after 24 months in retention the results remained stable.